2006
DOI: 10.1063/1.2165267
|View full text |Cite
|
Sign up to set email alerts
|

ITEP Bernas ion source with additional electron beam

Abstract: A joint research and development program is underway to develop steady-state intense ion sources for the two energy extremes of MeV and hundreds of eV. For the MeV range the investigations were focused on charge-state enhancement for ions generated by the modified Bernas ion sources. Based on the previously successful ITEP experience with the e-metal vapor vacuum arc ion source [e.g., Batalin et al., Rev. Sci. Instrum. 75, 1900 (2004)], the injection of a high-energy electron beam into the Bernas ion source di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…1 It was found that both the steady-state values of current discharge ͑I d = 260 mA͒ and the current of the extracted ions ͑I 1 = 10 mA for Sb +1 ͒ are in a good agreement with experimental data. 3 region͒ showed that the discharge could not start due to significant suppression of electron emission by the negative space charge.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 It was found that both the steady-state values of current discharge ͑I d = 260 mA͒ and the current of the extracted ions ͑I 1 = 10 mA for Sb +1 ͒ are in a good agreement with experimental data. 3 region͒ showed that the discharge could not start due to significant suppression of electron emission by the negative space charge.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…In the framework of investigation of low energy beam generation for ion implantation the ITEP version of Bernas ion source is used. [1][2][3] As the technology and applications continue to grow up, the development of plasma and ion sources with clearly specified characteristic are required. Therefore comprehensive numerical studies at the project stage are the key point for ion implantation source manufacturing.…”
Section: Introductionmentioning
confidence: 99%
“…The ITEP Bernas ion source ͑IS͒ with additional e-beam was used. 4 It was found that the highest decaborane negative ion current was extracted when the cathode and anode of discharge chamber are electrically connected ͑short circuit between them͒. The experiments with both the convenient polarity and the inversed one at the discharge electrodes resulted the significant decrease of extracted current.…”
Section: Decaborane Negative Ion Generationmentioning
confidence: 94%
“…10 Figure 2͑a͒ is a schematic of the ITEP Bernas ion source. After optimizing the electron beam charge states as high as Sn +6 were measured by magnetic separation.…”
Section: High Charge State Ion Sourcesmentioning
confidence: 99%